Pension Patterns in Sub-Saharan Africa - Dorfman, Mark (World Bank Group, Washington, DC, 2015)
This report provides an initial stocktaking of the characteristics, environment and performance of public and private pensions and elderly assistance programs in Sub-Saharan Africa. It identifies key challenges and suggests reform options for consideration. Considerations for future work and principles for pension policies are also suggested. Two major challenges noted in the report are the need to increase coverage of the labor force by pensions and social insurance schemes, and to increase the proportion of poor elderly covered by social assistance. The report suggests that improving coverage will require a number of parametric reforms to existing contributory schemes, strengthening institutions to serve informal sector workers, and piloting new design options. The report also proposes other parametric reforms, including the harmonization or merger of civil service and national pension schemes. Finally, the report recommends principles to consider for reform, including measures to improve coverage, protect the elderly poor, and better align pension design with needs and enabling conditions, including the needs of rural and informal sector workers.